Whole foods market takeover by Amazon.com - Brites, Afonso (2018)
The case-study describes the situation involving Whole Foods Market, Jana Partners and Amazon. The case-study describes the situation for Whole Foods Market and the shareholder activism by Jana Partners leading up to the take-over bid announcement by Amazon on June 16th 2017, when the Whole Foods Market management team invited shareholders to a special meeting to vote on the approval of the merger. The accompanying teaching note for the case-study addresses the financial analysis and valuation of Whole Foods, the rationale behind the merger, value creation through shareholder activism and the EPS fallacy as a measure of value creation.